The culture of “achoramiento”. New strategy of social mobility - Medina, Oswaldo (1998)
This article introduces the concept of "achoramiento" to describe a certain type of personal and institutional behavior, which essentially consists of breaking existing social norms in order to obtain personal benefits in terms of power, prestige, and especially money. The main argument is that "achoramiento" is a vernacular concept which nonetheless disguises a more general attitude prevalent in Peru today, and which is activated by certain conditions inherent to the current neoliberal economic model: limited opportunities for legitimate social mobility, absence of legal and institutional accountability, and widespread transgression of existing social norms and legal rules (including the Constitution) by the most powerful social and political actors, including central government officials and public and private enterprises. The article concludes that "achoramiento" should be seen as an alternative strategy for social mobility, based on a Machiavellian pragmatism and the turning of human relations into sheer market relations, which is in turn the product of an economic system that is increasingly concentrating  power and resources, is exclusionary, unregulated and dehumanizing.